Design of stainless steel cross-sections for simple load cases with the O.I.C. (May 2020) - Gagné, Anne-Sophie; Gérard, Lucile; Boissonnade, Nicolas
Abstract: The present paper investigates the resistance of stainless steel I or H sections as influenced by yield extent and local stability issues. In particular, the influence of a rounded stress-strain law with large strain hardening effects on the buckling response of sections is studied. Extensive shell non-linear numerical parametric studies led to a 750+ dataset that considered various material grades, 50 different section shapes (from compact to slender) and either sections in compression or under major-axis bending. These results allow to assess the merits of a design proposal based on the Overall Interaction Concept (O.I.C.) that is shown to be both very effective and accurate while remaining simple. The various influences of section's slenderness, section shape and steel grade are studied, and comparisons with alternative design proposal and design specifications evidence an increased level of accuracy, consistency and safety.